MEDIATING EFFECTS OF ISLAMIC BUSINESS SUCCESS ON PRODUCTIVE ZAKAT AND MUSTAHIQ WELFARE - Ivan Rahmat Santoso; Syahrir Mallongi; Siradjuddin; Muhammad Basir Paly (International Journal of Business and Society, 2024)
This research aims to determine the effect of productive zakat programs, entrepreneurial motivation, and competence on the welfare of mustahiq through having successful Islamic businesses as interveners. The research applied quantitative analysis method by distributing questionnaires to collect primary data from 111 mustahiq recipients of assistance from zakat institutions. This research employed a path analysis technique with the help of the SEM-PLS (Partial Least Squares) 4.0 program and was used to analyze the influence among variables. The empirical findings indicate that the productive zakat program significantly and positively affects mustahiq's welfare but not the business’s success. Meanwhile, entrepreneurial motivation and competence also significantly and positively affect business success and mustahiq welfare. Interestingly, the success factor for Islamic businesses can mediate the relationship between productive zakat, motivation, and competency on the welfare of mustahiq. This research contributes to the zakat literature by examining the connection between productive zakat, entrepreneurial drive, competency, and the factors influencing the performance of Islamic enterprises in achieving welfare according to Islamic objectives. Practically, the implications of this research are useful for the government as a policymaker in increasing the contribution of zakat institutions to material and spiritual poverty alleviation.